1977
DOI: 10.1007/bf02207866
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of estuarine ecosystems to effluent from pulp and paper industry

Abstract: A major problem associated with the discharge of pulp or paper-mill effluent into shallow estuarine ecosystems, such as the upper L'Etang in Canada or the Don in Scotland, is the development of anoxic conditions in water column and sediment. The effluent modifies the balance, within the ecosystem, between the supply of, and demand for, oxygen. The lignosulphonate component of pulp-mill effluent blocks the transmission of light energy to photosynthetic green plants. The oxygen demand is increased by the microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…This was unexpected because a larger volume of wastes was produced by the larger biomass of salmon in the market year (2002). It is possible that the anaerobic bacteria present in the sediment had undergone a self-poisoning event (due to high H 2 S ) earlier in the summer of 2002, as found by Poole et al (1977) and Marvin-DiPasquale & Capone (1998). High porosity, organic matter, carbon and nitrogen contents of sediments at the farm site, coupled with relatively low sulfide levels, supports the view that the wastes were accumulating in 2002 at rates much greater than the rate of decomposition by anaerobic sulfate-reducing bacteria.…”
Section: Resultsmentioning
confidence: 93%
“…This was unexpected because a larger volume of wastes was produced by the larger biomass of salmon in the market year (2002). It is possible that the anaerobic bacteria present in the sediment had undergone a self-poisoning event (due to high H 2 S ) earlier in the summer of 2002, as found by Poole et al (1977) and Marvin-DiPasquale & Capone (1998). High porosity, organic matter, carbon and nitrogen contents of sediments at the farm site, coupled with relatively low sulfide levels, supports the view that the wastes were accumulating in 2002 at rates much greater than the rate of decomposition by anaerobic sulfate-reducing bacteria.…”
Section: Resultsmentioning
confidence: 93%
“…Previous studies in temperate estuarine sediments enriched with pulp mill fibers (Poole et al 1977) have shown seasonal changes in composition of a benthic microbial community that was thought to reflect sulfide toxicity. H2S produced by sulfate-reducing bacteria, through anaerobic respiration stimulated by available substrate and increasing temperature during early summer, accumulated within sediments to levels that were toxic to benthic macrofauna and heterotrophic microflora.…”
Section: Discussionmentioning
confidence: 99%
“…H2S produced by sulfate-reducing bacteria, through anaerobic respiration stimulated by available substrate and increasing temperature during early summer, accumulated within sediments to levels that were toxic to benthic macrofauna and heterotrophic microflora. Poole et al (1977) suggested that at high H2S concentrations, metabolic activities of cellulolytic anaerobic and other non-heterotrophic bacteria that produce substrates (for example, lactate, pyruvate, malate) could be impaired. Since sulfate-reducing bacteria utilize these organic compounds as carbon and energy sources, inhibition of substrate production would limit sulfate reduction.…”
Section: Discussionmentioning
confidence: 99%
“…2) show that POM settled rapidly regardless of seasonal flow rates. Such input of organic material to the sediment can increase O 2 demand, and alter bacterial populations and processing (24). Increased nutrient concentrations mid-estuary (salinity ~22) in summer and winter were at a single site (Prince of Wales Bay), and likely relate to effluent discharge from a nearby STP.…”
mentioning
confidence: 99%